Property in East Central Europe - Hannes Siegrist , Dietmar Müller (Berghahn Books, 2014)
The epoch-making events of 1989 led to a spectacular renaissance of private property rights as a value and institution in the societies of Eastern Europe. In the minds of post-communist elites, shifting away from the statist socialist system would, in addition to changing the political system to parliamentary democracy, deeply affect the socio-economic and cultural sphere by restructuring society as the domain of private property owners. This great expectation indicates that the issue of property rights remains key to understanding the history of modern states and societies.1 In the present volume, historians, lawyers and cultural anthropologists analyse the issue of landownership in twentieth-century East Central Europe to understand and explain how and why Poles, Romanians and Serbs shape and use proprietary institutions in projects of social, political, economic, cultural and legal ‘modernization’. Their contributions show why societies that were largely dependent on agriculture well into the twentieth century have adapted traditional forms and developed hybrid and new types of property.2 Special attention is devoted to the years around 1918, 1945 and 1989, when concepts of property and the role of property rights in the social and political sphere changed fundamentally. This volume analyses the social, cultural, economic, legal and political meanings and functions of property rights in East Central Europe, investigating processes, structures, institutions, practices and mentalities in short-, mid- and long-term historical perspectives and at the macro-, meso- and micro-levels. Through comparative analyses of cases from three different countries, and of the institutional transfers between them, it aims to improve understanding of differences and similarities between nations, sub-national regions and transnational property cultures, and to help overcome some of the idiosyncrasies of single-nation historiographies, which rarely look across borders. At the same time, it challenges certain stereotypes in the international and Western historiography of East Central Europe